2014
DOI: 10.1186/1756-3305-7-335
|View full text |Cite
|
Sign up to set email alerts
|

Complete mitochondrial genome sequences from five Eimeria species (Apicomplexa; Coccidia; Eimeriidae) infecting domestic turkeys

Abstract: BackgroundClinical and subclinical coccidiosis is cosmopolitan and inflicts significant losses to the poultry industry globally. Seven named Eimeria species are responsible for coccidiosis in turkeys: Eimeria dispersa; Eimeria meleagrimitis; Eimeria gallopavonis; Eimeria meleagridis; Eimeria adenoeides; Eimeria innocua; and, Eimeria subrotunda. Although attempts have been made to characterize these parasites molecularly at the nuclear 18S rDNA and ITS loci, the maternally-derived and mitotically replicating mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
26
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 43 publications
(77 reference statements)
2
26
0
Order By: Relevance
“…(8 from chickens, 6 from the domestic turkeys (Ogedengbe et al, 2014), 6 from rabbits (Liu et al, 2015;Tian et al, 2015) and one from a striped skunk (Mephitis mephitis).…”
Section: Phylogenetic Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…(8 from chickens, 6 from the domestic turkeys (Ogedengbe et al, 2014), 6 from rabbits (Liu et al, 2015;Tian et al, 2015) and one from a striped skunk (Mephitis mephitis).…”
Section: Phylogenetic Analysesmentioning
confidence: 99%
“…Among the apicomplexan organisms, Eimeria is phylogenetically closest genus to Isospora based on 18S gene sequences (Yang et al, 2015a). The complete mt genome sequences for 19 Eimeria species have been reported (Hikosaka et al, 2010;Lin et al, 2011;Liu et al, 2012 and2015;Heitlinger et al, 2014;Ogedengbe et al, 2014;Hafeez et al, 2016;Tian et al, 2015), all of which range from 6.1 to 6.4 kb in size with highly conserved content and structure (Liu et al, 2015). Currently only one Isospora mt genome sequence has been reported .…”
mentioning
confidence: 99%
“…Amplification was performed using a Veriti® 96-well Thermal Cycler (Applied Biosystems, Foster City, CA). The primers used were kindly provided by Dr. John R. Barta (University of Guelph, ON, Canada) and their sequences (Ogedengbe et al 2014) are shown in Table 1. The reaction mixture for each sample comprised 5 μL (20 ng) of gDNA, 12.5 μL of PCR master mix (Promega Corporation, Madison, WI), 400 nM forward primer, 400 nM reverse primer, and nuclease-free water to make up a final volume of 25 μL.…”
Section: Polymerase Chain Reactionmentioning
confidence: 99%
“…(see Ogedengbe et al, 2013, 2014) failed repeatedly with C. cayetanensis . Thereafter, shorter regions of the mt genome were amplified with primers targeting conserved regions of other apicomplexan mitochondrial genomes.…”
mentioning
confidence: 99%
“…These efforts failed repeatedly with C. cayetanensis but succeeded in the case of coccidia in the genera Eimeria, Caryospora and Isospora (e.g. Lin et al, 2011; Ogedengbe et al, 2013, 2014; 2015; Ogedengbe and Barta, 2015), all of which possess circular-mapping mt genomes; Eimeria tenella was used as positive control for all such PCRs due to its linear concatenated genome.…”
mentioning
confidence: 99%